2019
DOI: 10.3390/ijerph16245056
|View full text |Cite
|
Sign up to set email alerts
|

Rural Work and Specialty Choices of International Students Graduating from Australian Medical Schools: Implications for Policy

Abstract: Almost 500 international students graduate from Australian medical schools annually, with around 70% commencing medical work in Australia. If these Foreign Graduates of Accredited Medical Schools (FGAMS) wish to access Medicare benefits, they must initially work in Distribution Priority Areas (mainly rural). This study describes and compares the geographic and specialty distribution of FGAMS. Participants were 18,093 doctors responding to Medicine in Australia: Balancing Employment and Life national annual sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Flexible training options, supportive team practices with sufficient staff relief, salaried employment options, female-tailored continuing professional development topics, and robust social and professional network opportunities may be important strategies to attracting more females to this workforce [ 44 , 46 , 47 ]. Previous research has demonstrated the linkage between female GPs having children and relocations to more urban settings, with the same effect on males only occurring when the children are of secondary school age [ 48 ]. There appears to be a strong scope for rural faculties to play a role in accommodating the tailored employment and family needs of doctors.…”
Section: Discussionmentioning
confidence: 99%
“…Flexible training options, supportive team practices with sufficient staff relief, salaried employment options, female-tailored continuing professional development topics, and robust social and professional network opportunities may be important strategies to attracting more females to this workforce [ 44 , 46 , 47 ]. Previous research has demonstrated the linkage between female GPs having children and relocations to more urban settings, with the same effect on males only occurring when the children are of secondary school age [ 48 ]. There appears to be a strong scope for rural faculties to play a role in accommodating the tailored employment and family needs of doctors.…”
Section: Discussionmentioning
confidence: 99%
“…However, P-IMGs seemed to be more likely to join these specialties and fill the critical gaps, as with those in the US [ 45 ]. We found papers stating that IMGs in the US tend to practice in primary care specialties [ 46 , 47 , 48 ], as did foreign medical graduates in Australia [ 4 ]. Another paper found that IMGs practiced more in four specialties: internal medicine, neurology, psychiatry, and pediatrics [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The term “international medical graduates” (IMGs) is generally understood to denote a physician who is awarded their medical degree in a country other than the one where they intend to practice medicine [ 1 , 2 , 3 ]. Over recent decades, IMGs have played a significant and expanding role in medical practice in many developed countries throughout the world, constituting approximately 31% of physicians in the United Kingdom, 25% in the United States, 17% in Australia, and 23% in Canada [ 1 , 4 ]. The wave of globalization, an aging population with increasing demands for medical care, and the pursuit of a better quality of life could all be reasons for this phenomenon [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter example are perhaps more likely to work long-term in rural Victoria if given the opportunity to return to Victoria and take up a rural internship. International graduates in comparison are less likely to have any connection to rural areas they are applying to undertake an internship in, as the government-funded rural training opportunities during medical school (Rural Clinical School training immersion) is largely reserved for domestic students [ 25 , 26 ]. They are also unlikely to have spent childhood periods in rural Victoria.…”
Section: Discussionmentioning
confidence: 99%
“…Australia's key regulatory policy since 1996 has required overseas trained doctors and international students graduating from Australian medical schools to work in Districts of Workforce Shortages (DWS) (mainly in rural areas) for up to 10 years after they enter the medical workforce, in order to gain a provider number for access to Medicare billing. This policy's 'success' is strongly associated with Australia's current high reliance on OTDs to supply its rural medical workforce [24,25]. As such, growing the number of domestic graduates who enter and remain in Australia's rural workforce remains a key priority.…”
Section: Australian Policiesmentioning
confidence: 99%